Subjective well-being of current and former elite athletes in the German armed forces - Peter Ehnold; Franziska Vollmann; Torsten Schlesinger (Frontiers Media S.A., 2024)
IntroductionThe German military's sports promotion group (SPG) is an entity that aims to minimize the risks inherent in elite sports careers. Risks that manifest themselves, for example, in a lack of financial resources or failed dual careers could undermine the subjective well-being (SWB) of athletes, which can have a negative impact on athletic performance. A differentiated understanding of factors that influence SWB is therefore necessary.MethodsWithin the scope of a survey, a sample of n = 414 current and n = 298 former sports soldiers was generated. Linear regression models (blockwise) were used to analyze the influence of the SPG framework conditions, the influence of top sport-specific factors, and the influence of socio-demographic/socio-economic factors on the SWB of current and former sport soldiers.ResultsCurrent and former sports soldiers showed high satisfaction scores and were also optimistic about the future. Among current sports soldiers, men had higher SWB values. In addition, satisfaction with SPG services, satisfaction with their athletic careers, and satisfaction with their current income all influenced the athletes' SWB. Among former sports soldiers, persons in a stable partnership had higher SWB values. Furthermore, satisfaction with SPG services, a career end that was perceived as involuntary and satisfaction with current income were relevant for SWB in this cohort.DiscussionThis study addresses the call for a more athlete-centered approach in sports science research and the findings have several implications for organized sports to promote SWB in elite athletes.